Variation in Diurnal Patterns of Singing Activity Between Urban and Rural Great Tits - Bermúdez-Cuamatzin, Eira; Delamore, Zoë; Verbeek, Laura; Kremer, Christoph; Slabbekoorn, Hans (Frontiers in Ecology and Evolution, 2020)
Human settlements and activities alter the natural environment acoustically and visually. Traffic noise and street lights are two of the most prominent pollutants which may affect animal activity patterns. Birds in urban areas have been reported to sing nocturnally and to have an earlier dawn chorus compared to their rural counterparts. However, few studies have measured whether singing more at night or earlier in the morning means singing less during daytime. It is therefore unclear whether they shift or extend or overall increase their activities. Furthermore, few studies on anthropogenic noise related shifts in song activity replicated well at the habitat level. We recorded singing activity in urban and rural great tits (Parus major) for 24 hours and sampled eleven urban-rural pairs of territories, inside and outside eleven different cities across the Netherlands. We found that urban birds sing earlier during the day, have similar singing effort in the dawn chorus, but sing less than rural birds during the rest of the day. The shift in timing between urban and rural birds was 22 minutes on average and resulted in more songs for urban birds during a less noisy time of the day. The lower singing activity over the day made that urban birds sang less when it was more noisy compared to the natural rhythm of rural great tits. We currently lack insight into whether these differences yield any positive or negative fitness consequences, but it is a clear case of how anthropogenic effects on the natural environment influence fundamental aspects of daily life in the animal communities with which we share the urban habitat.